Experimental validation for chatter stability prediction - Muhammad Azwan, Zainol Abidin (2012)
This research focused on the experimental validation for chatter stability prediction. An optimum machining was aimed to maximize the material removal rate, whilst maintaining a sufficient stability margin to assure the surface quality. High material removal rate in machining produced self-excited vibration or chatter of the cutting tool and the workpiece. This resulted in a poor surface finish and dimensional accuracy, chipping of the cutter teeth, and also may damage the workpiece as well as machining tool. Frequency response function of a single degree freedom flexural was measured and the cutting stiffness of tools were determined in order to be used in predicting chatter stability using semi discretization method. The aluminium 7075 specimens were used in the milling cutting experiment to validate the chatter stability diagram of mill uniform and variable cutters, where a set of spindle speed and depth of cut had tested. The vibration conditions of machining were identified by analysing the vibration signals and FFT spectrum whether it was stable or in a chatter condition. There are good agreement between predicted stability and cutting experiment for the down-milling operation using uniform 4 flute cutting tool. Stable conditions were shown outside the boundary of chatter region. The optimized cutting tool was predicted to suppress chatter. Machining experiment tests showed there were no chatter vibration conditions during machining process until 1.5 mm depth of cut. According to the results of machining experiment, it was proven that the variable tool had more capability to machining without producing chatter vibration as compared to the regular tool.